Effort To Improve Elementary Students Interest On Music Subject With “Learning By Doing” Method Class: (Case Studies of School Curriculum in Music Education) - Dani Nur Saputra (ADI Publisher, 2021)
Elementary student’s interests in music subjects at baseline showed a low percentage that is equal to 53.29%. Therefore it is necessary to attempt to increase student’s interest towards the subject. Learning by doing method applied to grade students in elementary school of Sukorejo, Indonesia to increase student’s interest towards music subject. The method that used is descriptive qualitative and quantitative descriptive (mixing methods). Data was collected by questionnaire (questionnaire), observation, interviews, and documentation. The results showed that the learning model of learning by doing can improve student’s interest towards music subject at 94.73% and also can cultivate student’s interest during the learning process and can foster student’s interest towards music activities. In these efforts need to be supported facilities complete musical equipment of schools and teachers should be reproduce musical activities (practices) in the process of learning the art of music and requires students to take an active role in the learning process such as to ask, give an opinion and doing musical activities in the classroom.